Bridging Digital Divide in Education: A Systematic Review (SLR-PRISMA) of Digital Inclusion Strategies - Badrud Tamam; Ahsantudhonni; Aminudin; Muthahharah Thahir; Asti Putri Kartiwi (Jurnal Pendidikan dan Pengajaran, 2026)
The digital divide in education remains an important issue affecting equitable access and the quality of learning. This study aims to analyze the development of research on the digital divide in education and digital inclusion strategies. This research employed a qualitative approach using a Systematic Literature Review design based on the PRISMA protocol. The research subjects consisted of indexed scientific articles published in national and international journals relevant to the topics of the digital divide and digital inclusion in education. Data collection was conducted through documentation studies of articles obtained from scientific databases, using instruments in the form of inclusion–exclusion criteria sheets, data extraction tables, and literature analysis matrices. Data analysis was carried out through thematic analysis and bibliometric analysis. The results showed that the focus of digital divide studies has shifted from issues of technology access and digital literacy during the pandemic period toward technology-based pedagogical innovations, including the use of Artificial Intelligence (AI) and Virtual Reality (VR) to support inclusive education. In addition, socio-economic and gender factors were found to have a significant influence on the success of students’ digital literacy. This study concludes that efforts to overcome the digital divide require the comprehensive integration of social, technological, and educational policy aspects. The implications of this study emphasize the importance of educational institutions designing technology-based learning strategies that are inclusive, adaptive, and accessible to all learners.